PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PUBLIK DI INDONESIA - Sairin, Sairin (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to analyse the effect of audit quality on earnings management practices in public companies listed on the Indonesia Stock Exchange (IDX). Audit quality is proxied by the size of the Public Accounting Firm (KAP Big-4 and non Big-4), audit tenure, and audit fees, while earnings management is measured using the modified Jones discretionary accrual model. The research sample consists of 120 non-financial public companies listed on the IDX for the 2021-2023 period. The analysis method used is multiple linear regression with data processing using SPSS version 26. The results showed that: (1) KAP size has a significant negative effect on earnings management; (2) audit tenure has a significant positive effect on earnings management; and (3) audit fees have a significant negative effect on earnings management. This study contributes to the accounting literature regarding the importance of audit quality in limiting earnings management practices in Indonesia by using current data and a comprehensive approach.